Perbandingan Makna Ideasional Representasi Tiga Pemimpin dalam Novel A Clash of Kings dan Terjemahannya - Hilma Rabbani; Haru Deliana Dewi (Riviera Publishing, 2025)
This research wil discuss the representation of three leaders in the novel A Clash of Kings by George R. R. Martin. The three leaders discussed are Stannis Baratheon, Joffrey Baratheon, and Daenerys Targaryen. The three characters will be assessed with the critical discourse analysis approach of Halliday's ideational metafunction theory (2004). This research will examine the representation of the three leaders shown through their ideational functions by observing the transitivity of their clauses in the original version and their translation, then comparing the results of the analysis of the two versions. The research method is descriptive qualitative and data corpus processing using Sketch Engine tool to see transitivity in the depiction of the three characters and compare it with the translated version. The results showed that the characters Stannis and Joffrey were dominated by material processes (34.7% and 46% in the original text; 37.95% and 40% in the translation, respectively), while Daenerys was dominated by mental processes (45.8% in the original text; 48% in the translation). The shift in transitivity occurs due to differences in language and cultural structure, but it does not significantly affect the overall image of the character. The conclusion of this research is that the composition of process types affects the figure of the leader represented by each character. In addition, based on the process type components of the characters, there is no significant shift in the representation of the characters in the translated version. Research on this topic is expected to see how the translation process affects the ideational function in interpreting human experience.